UPAYA KEPALA MADRASAH DALAM PENINGKATAN KINERJA GURU DI MADRASAH ALIYAH BAHRUL ULUM MULIASARI - Zainudin Zainudin (Conciencia, 2015)
The quality of education of a nation will determine the future of the nation itself in the sense that education is a very important requirement in determining the future development of the nation. The superiority of a nation is no longer characterized by the abundance of natural resources, but the benefits of human resources. Its quality is positively correlated with the quality of education, and quality of education is often indicated by the condition of good, qualified, and all the components that should be included in education. These components are the inputs, processes, outputs, staff, facilities, infrastructure, and cost. Deterioration of the quality of learning outcomes of students is not only caused by a lack of motivation to learn, lack of parental supervision, or weakness on the part of the teacher, but the factors that influence is strong enough madrassa management improper use and is not appropriate. To that end, one of the efforts to be made in improving teacher performance is through the optimization of the role of headmaster. Headmaster as a driving force performance improvement teachers are required to have a vision, mission, and extensive knowledge and adequate professional skills in planning, organizing, implementation, and supervision of education. In addition, the staff is required to have the ability to build harmonious cooperation with the various parties concerned with the education program at the school. The ability headmaster of course will also influence the performance of teachers in performing the task. One indicator of the performance of the headmaster is assessed on the basis of competence and performance of duties and responsibilities.